GOOGLE CLASSROOM MEDIA EFFECTIVENESS ON STUDENT LEARNING OUTCOMES IN THE COGNITIVE REALM IN FIQH SUBJECTS - Mashuri, Imam; Faishol, Riza; Dandy, Muhammad; Ziyaad, Khalid (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This research was motivated by the COVID-19 pandemic that hit the entire world, including in Indonesia, because of the nature of the virus that is able to spread quickly and is very dangerous, the government has made preventive efforts by making policies to carry out social distancing and physical distancing. This type of thesis research is quantitative research with a True Experimental Design approach. The population in this study was all XI MAN 2 Banyuwangi students totaling 432 students. The sample of this study was to take the cluster sampling technique, namely class XI Religion 2 with a total of 36 students. Data collection techniques in this study used observation, interviews and tests (pretest and posttest), and documentation. Then for test analysis using the t test technique. The research data was obtained with the results of a multiple-choice type online test of 25 questions with pretest and posttest categories, then analyzed using prerequisite tests and hypothesis tests using paired sample t-test tests. The results of the research obtained were the results of learning jurisprudence subjects using Google Classroom media with paired sample t-test with the help of the SPSS application version 16 obtained the results that: The value of ttabel < thitung value (21,780 > 2,030 with a signification level of 5%, and the sig value. (2-tailed) of 0.000. With a correlation value from the pretest to posttest values of 0.966 so that based on the index table the correlation coefficient is classified as very strong. So, it can be concluded that there is an effectiveness of Google Classroom media on student learning outcomes in class XI jurisprudence subjects at MAN 2 Banyuwangi.